A Review on Failure Characteristics of Polymer Gear - Wafiuddin, Md Ghazali; D. M. N., D. Idris; Azizul Helmi, Sofian; Siregar, J. P.; M. S. S., Edrus (EDP Sciences, 2016)
Polymer are now widely used as substitute material for steel in low load devices. Its failure differs from gears made of steel, thus it is important to categorize the failures shown by polymer gears. Several previous studies noted that wear detection, microstructure surface condition monitoring, weight loss and temperature detection can be used in detecting failure of polymer gear. This article reviews the failure detection method mentioned above. Other researcher works were studied and their findings were extracted in order to identify the methods they used. The most common method used was wear detection and it was supplemented by other methods such as microstructure surface condition monitoring. Failures shown by polymer can be concluded to be tooth breakage, tooth deformation, material removal and surface fatigue.